Longitudinal Impact of the COVID-19 Pandemic on Older Adults' Wellbeing - López, Javier; Pérez-Rojo, Gema; Noriega, Cristina; Martínez-Huertas, Jose Angel; Velasco, Cristina (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic could be considered a major stressful life event. This pandemic has provoked a disruption of daily life with a great impact on older adults´ physical and mental health. Nevertheless, psychological well‐being plays a protective role in coping with adverse circumstances, such as the COVID-19 pandemic. This study aims to assess the impact of COVID-19 on older adults´ psychological wellbeing (personal growth and purpose in life) over time. Materials and Methods: 192 older adults took part in a longitudinal survey collected on March 2020 (during the lockdown restrictions) and at two subsequent time points 4 and 10 months after baseline (without lockdown restrictions and during the third wave of the pandemic respectively). Different latent growth curve models were used to estimate the linear longitudinal trajectories of psychological wellbeing. Results: Older adults did not evidence poorer psychological wellbeing than during the initial lockdown. Age has a positive impact on purpose in life. Furthermore, being a male, worrying about adverse effects of COVID-19, family functioning, resilience, personal growth and acceptance had significant associations with purpose in life. Discussion: The ﬁndings in this study support that older adults may adapt to the adverse pandemic impact by using more adaptive resources that strengthen their wellbeing.